2011
DOI: 10.1158/1535-7163.mct-10-0754
|View full text |Cite
|
Sign up to set email alerts
|

Enigmol: A Novel Sphingolipid Analogue with Anticancer Activity against Cancer Cell Lines and In vivo Models for Intestinal and Prostate Cancer

Abstract: Sphingoid bases are cytotoxic for many cancer cell lines, and are thought to contribute to suppression of intestinal tumorigenesis in vivo by ingested sphingolipids. This study explored the behavior of a sphingoid base analog, (2S,3S,5S)-2-amino-3,5-dihydroxyoctadecane (“Enigmol”), that cannot be phosphorylated by sphingosine kinases and is slowly N-acylated, therefore, is more persistent than natural sphingoid bases. Enigmol had potential anti-cancer activity in a National Cancer Institute (NCI-60) cell line … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 47 publications
(55 reference statements)
2
63
0
Order By: Relevance
“…Over the duration of treatment, animals receiving 5a, 5b, and 5c experienced significantly slower tumor growth rates than those treated with vehicle (p = 0.02, 0.01, and 0.01, respectively, using the mixed model for repeated measurements). The degree of tumor growth inhibition by enigmol (5a) was similar to that seen in previous PC-3 xenograft studies, 15 as well as in the PC-3 docetaxel study ( Figure 3B), highlighting the reproducibility of in vivo efficacy with enigmol. Differences in tumor growth rates were not statistically significant in N-methylenigmol versus controls.…”
Section: Scheme 1 Synthesis Of Enigmol (5a) and Its 2s-diastereomerssupporting
confidence: 84%
See 2 more Smart Citations
“…Over the duration of treatment, animals receiving 5a, 5b, and 5c experienced significantly slower tumor growth rates than those treated with vehicle (p = 0.02, 0.01, and 0.01, respectively, using the mixed model for repeated measurements). The degree of tumor growth inhibition by enigmol (5a) was similar to that seen in previous PC-3 xenograft studies, 15 as well as in the PC-3 docetaxel study ( Figure 3B), highlighting the reproducibility of in vivo efficacy with enigmol. Differences in tumor growth rates were not statistically significant in N-methylenigmol versus controls.…”
Section: Scheme 1 Synthesis Of Enigmol (5a) and Its 2s-diastereomerssupporting
confidence: 84%
“…In vitro, enigmol inhibits both sphingosine kinase and ceramide synthase, 14,15 and it has demonstrated potent anticancer activity in cells derived from multiple types of cancer, including colon, breast, brain, and prostate. 15 Furthermore, in rodent ACS Medicinal Chemistry Letters LETTER models of colon and prostate cancers, enigmol has shown significant oral efficacy, with no evidence of host toxicity at effective doses. Mass spectrometry of lipids extracted from cancer cells treated with enigmol has shown that enigmol is not phosphorylated and, as predicted by our original rationale, was more cytotoxic and more persistent as a free sphingoid base than as an exogenous sphingosine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of the importance of dietary sphingolipids in fighting colorectal cancer was first described by Dudeja et al (1986), who found differences in both sphingolipid composition and sphingolipid enzyme activities between tumor and normal tissue. Certain sphingolipids are also active against other cancer types, such as enigmol, a sphingoid base analog (Symolon et al, 2011). Sphingoid bases are cytotoxic for many cancer cell lines and are thought to contribute to suppression of intestinal tumorigenesis in vivo by ingested sphingolipids.…”
Section: Effects Of Sphingolipids On Cancermentioning
confidence: 99%
“…Sphingadiene (Kumar et al, 2012) and Enigmal (Symolon et al, 2011) a derivative of sphingolipid potentially reduces the expression as well as, controls the translocation of non-p-β-catenin in APC min mice and colon cancer cells through inhibiting pGSK3β. Similarly Luteolin, a flavone present in green pepper, perilla leaves and peanut inhibits the expression of non-p-β-catenin mediated by the inhibition pGSK3β in AOM-induced colon carcinogenesis.…”
Section: 2201 Potential Targets For Prevention Of Colorectal Cancer:mentioning
confidence: 99%